Literacy of Patient with Experience of Mental Illness - Methods of Health Education and Psychoeducation in Mental Health Nursing [Póster] - Dias, Carlos Manuel de Melo (2014)
Introduction Coping with our transitions (Meleis, 2010) or satisfying our human needs (Henderson, 2001) is a demand for each of us. Be knowledgeable and reflect about this knowledge is crucial to maintain health, prevent or treat problems/disturbances. Nurses are able to do it, but they need clearly knowing, what patients know about themselves and the illness? And about coping with that all? How nurses teach and train patients? About what? Which methods and strategies they prefer and are evidence based practice? General Objective In our point of view literacy of Patient with Experience of Mental Illness (PEMI) is strongly sensitive to nursing interventions therefore the intrinsic concern is about establishing a basis for developing knowledge in nursing and improving practice focused on health education methods and strategies within nursing care. Methodology For the first step, it is important acknowledge literacy of PEMI as an dependent variable of clinical reasoning in nursing practice, intentionally done by the nurse, based on knowledge and experience, to systematically select, compare, test, infer and decide on the specific clinical evidence of the clinical course of the patient, generating clinical decisions and conclusions that achieve the expected results (Melo-Dias & Lopes, 2010). We use a critical structured reflective inquiry as a method to consciously examine what has occurred in terms of thoughts, feelings and actions against underlying beliefs, assumptions and knowledge as well as against the context in which specific situation has occurred (Kim, 1999). Involving the above definitions and principles, this critical structured reflective inquiry consists in three phases (Kim, 1999; Queirós et al, 2000; Santos e Fernandes, 2004; Santos, 2009) namely: descriptive, reflective, and critique/emancipatory. Results The descriptive phase contains the descriptions of thoughts, feelings, circumstances and features of the situation of caring for a PEMI, questioning about: Who is this person? What features have the situation? What the patient knows about itself and about the disease? What the patient knows about health, and mental health? What or how I felt? Why this subject is significant to me? The reflective phase contains the analysis about what happen in the terms of thoughts, feelings and actions against underlying beliefs, assumptions and knowledge. This reflection has three different foci: against ourselves, against contextual features, including the colleagues, and against scientific knowledge. Also we shall drive through: did I Intervened on disease knowledge, on health knowledge, on knowledge of himself, or on all? I worked on this aspect, what I did and how I did it? What is the best approach to this subject? At last, the critique/emancipatory phase is orientated to correcting and changing less-than-good or ineffective practice or moving forward to future assimilation of new innovations emerging from practice. Conclusion In the end we shall present new knowledge through this investigation of knowledge embedded in practice, exposing what is nursing, helping teaching nurses, sharing learning, helping nurses reasoning critically and constructively, increasing confidence, security and competence on nurse performance, within PEMI mental health literacy and Nursing methods and strategies to teach and train patients to achieve healthy coping ways to deal with oneself, with the illness, and with the life as it is.